RIAP PERTUMBUHAN JATI UNGGUL NUSANTARA ROTASI KEDUA DI KEBUN PERCOBAAN COGREG UNIVERSITAS NUSA BANGSA - Meiganati, Kustin Bintani (Universitas Nusa Bangsa, 2017)
The copies JUN in the UNB Experimental Garden is the second rotation, this is an economic and ecological consideration. According to previous studies that sengon copies can be done in 3 rotations. JUN and sengon have similar physical characteristics of wood. The characteristics of the wood include the water content, density and density of wood. So that it is assumed, the growth of sengon stands also has similarities with the growth of JUN stands. In this research, it will be seen whether the JUN increment in the second rotation will produce results that are in line with expectations, and whether it will be feasible to continue in the third rotation. Riap in the second rotation will be a consideration for the next rotation. The prediction of increment in the next rotation can be calculated by knowing the increment in the second rotation. This study took a sample of 20% of the total population or as many as 1084 JUN copies stands. From this study it was concluded that the increment in the second rotation was 2.8 cm / year or decreased by 40%, so to obtain the lowest grade woodworking (AI) it took 7 years and 8 months. If it is continued in the third rotation it requires a cycle of 17 years 8 months to obtain an AI standard and requires a cycle of 26 years 8 months to obtain the AIII standard. From the results above, it is recommended that for JUN copies only until the second rotation because the predicted cycle is still below 10 years. The third rotation cannot be done because the growth of diameter increments is below 2 cm / year, so the cycle takes more than 10 years.Â Â